Pengaruh Komposisi Starter Pada Fermentasi Limbah Cair Tahu Terhadap Kadar Phosphor (P) - Muhammad Amin Faisal; Agung Rasmito; Bambang Sutejo (Jurnal Ilmiah Teknik Unida, 2023)
The liquid waste of the tofu making process still contains a lot of high phosphorus (P). Instead of being thrown away can pollute, it is used for fertilizer. In order to be easily absorbed by plants, it must be fermented. Tofu liquid waste fermentation process by adding banana peel, cabbage and EM4 bioactivator. The variable used the weight ratio of banana peel to cabbage on the starter, and also the duration of fermentation. In conclusion, the level of phosphorus is greater when the weight ratio of banana peel and cabbage is getting smaller, the highest level is obtained at a fermentation duration of 15 days.